MEKANISME PEMENUHAN HAK TERSANGKA MELALUI PENETAPAN TERSANGKA MENJADI OBJEK PRA PERADILAN - Fachruddin Razi (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
The existence of law No. 8 of 1981 on the book of the law of Criminal Procedure Law in the life of the law in Indonesia have been demanding a new era, that of the era of revival of national laws that give priority to the protection of the rights of a suspect in the criminal justice system mechanisms.Pretrial is essentially an institution to conduct surveillance against acts horizontally attempts forcibly against the suspect for being in the process of investigation and prosecution. Institutions that carry out the functions of the pretrial is the District Court. so it is only found in pretrial Court level alone. Pretrial is one of apparition of Habeas Corpus as a prototype, i.e. as a place to denounce violations of human rights ("HAM") in a criminal proceeding process (andi hamzah) pretrial legal Effort itself basically aims to protect the rights of suspects in connection with the acts of forced efforts that might be undertaken by investigators against the suspect. With the lawsuit regarding pretrial status of a suspect, it can expand the authorities of the institutions of the pretrial, can also make law enforcement more professional and more careful in setting a person becomes suspect.Keyword : fulfillment, the suspect, judicial